APLIKASI PERINTAH SUARA UNTUK OPERASI POWERPOINT - Sandy Kurniawan Ruhiat; Ucuk Darusalam; Benrahman Benrahman (J-Icon : Jurnal Komputer dan Informatika, 2021)
Microsoft PowerPoint is an application that is often used in presentations because of the ease of operation. Even so, users are still required to adjust the presentation manually such as starting a slide, continuing to the next slide, returning to the previous slide, and so on by pressing the keyboard button. Often, it is difficult for users to reach the computer while doing a presentation in front of many people and it will certainly take time. The purpose of this research is to reduce physical contact between users and computers by using voice instead of keyboard commands to operate the presentation so that it is more effective. This research implements the Hidden Markov Models base of Microsoft Speech API in C# programming language. The tolerance level of word pattern changes approaching the original word is 84.29% and the accuracy of the program running in the clear background is 100%. Users can use the application with a microphone or the like as input that is compatible with their computer.